Cigarette advertising in Cold War Bulgaria. (15th February 2016) - Neuburger, Mary Catherine
Abstract : Purpose: – This paper aims to explore the parameters of Bulgarian cigarette advertising in the Cold War period. It contrasts the evolution of cigarette marketing in Bulgaria and the USA in the context of contrasting communist and capitalist notions of the "good life" versus the "common good". Design/methodology/approach: – The paper is informed by a growing literature on advertising under communism, but also new work on consumption in the Soviet Union and Cold War Eastern Europe. It draws upon archival and printed Bulgarian, and some American, sources, and the memoir of a key player in the Bulgarian tobacco industry. Findings: – The paper concludes that marketing of cigarettes in communist Bulgaria gained momentum in the same period that cigarette advertising in the USA was severely curtailed. In Bulgaria, the notion that cigarettes were key to the promised "good life" and "building socialism", out-weighed any notion of harm to the "common good". Originality/value: – This study casts doubt on the common notion that there was no advertising under communism, by offering an in-depth study of an industry that was allowed to market and develop a quality product to an unusual degree. It undermines assumptions about "command" economy, industry behavior, contributing to a re-thinking of Eastern Bloc consumer culture. In addition, it sheds light on changes in the acceptability of cigarette advertising within the Cold War context, namely, how the process of advertising regulation in the West, and increased marketing in the East, fit into Cold War debates and interactions.